Case Report: Hypopituitarism Presenting With Nonconvulsive Status Epilepticus - Li, Huimin; Xu, Lina; Yang, Fengbing; Jia, Longbin; Cheng, Hongjiang; Liu, Wei (Frontiers in Neurology, 2021)
Hypopituitarism is defined as one or more partial or complete pituitary hormone deficiencies. Nonconvulsive status epilepticus (NCSE) refers to a state of continuous or repetitive seizures without convulsions. In this paper, we review a case of an old female patient with hypopituitarism who presented with nonconvulsive status epilepticus, which is rear in the clinic.